Why Bother About Clumsiness? The Implications of Having Developmental Coordination Disorder (DCD) - Christopher Gillberg; Björn Kadesjö (Neural Plasticity)
Developmental coordination disorder (DCD) is a common motor problem affecting—even in rather severe form—several percent of school age children. In the past, DCD has usually been called ‘clumsy child syndrome’ or ‘non-cerebralpalsy motor-perception dysfunction’. This disorder is more common in boys than in girls and is very often associated with psychopathology, particularly with attention-deficit/hyperactivity disorder (ADHD) and autism spectrum disorders/ autistic-type problems. Conversely, children with ADHD and autism spectrum problems, particularly those given a diagnosis of Asperger syndrome, have a very high rate of comorbid DCD. Psychiatrists appear to be unaware of this type of comorbidity in their young patients. Neurologists, on the other hand, usually pay little attention to the striking behavioral and emotional problems shown by so many of their ‘clumsy’ patients. A need exists for a much clearer focus on DCD—in child psychiatry and in child neurology—both in research and in clinical practice.